La théorie économique à l’épreuve de la covid-19 - Philippe Batifoulier (Association Recherche & Régulation, 2021)
The objective of this article is to show that the covid-19 crisis is not only pandemic. This crisis is also the one in which the mainstream economy thinks about health, in its different dimensions, and consequently how politics considers health. The covid-19 health crisis is a total and multidimensional crisis. Health issues must be seen as social issues and the fundamental right to health cannot be reduced to a mere application of the usual categories of neoclassical theory.